ANALISA PERUBAHAN GARIS PANTAI AKIBAT BANGUNAN PENGAMAN PANTAI (GROIN) DI PANTAI SALIDO PESISIR SELATAN SUMATERA BARAT - Hamidi, Wazer El; Junaidi, Junaidi; Junaidi, Ahmad; Hakam, Abdul (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
In 2015, the government, through the Regional Office V Sumatra River, building groynes and jetties to maintain of the Salido coastline. But development is limited to the Salido coastline, while Salido position is the one with the coastline of Sago which is located in the northwest. So, the author is interested to research whether the construction of groynes have an impact on areas that are not built and whether the groynes effective to deal with the instability of the coastline, by simulating changes in the coastline in the next 10 years. The study results also show that the groynes is effective in maintaining the stability of the Salido coastline. While the impact of groynes in areas not built is abrasion on the downstream side of the last groyne bordering the Sago coastline ± 78 meters, and the deterioration of the coastline ± 18 meters by simulating 10 years into the future. After the construction of groynes, Sago beach will no longer accreting or abrasion (accretion occurs earlier). Abrasion on the downstream side of last groins are likely to increase so that development needs to be done along the Sago shoreline.